2016
DOI: 10.1101/036475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A performance-optimized model of neural responses across the ventral visual stream

Abstract: 12Human visual object recognition is subserved by a multitude of cortical areas. To make sense 13 of this system, one line of research focused on response properties of primary visual cortex 14 neurons and developed theoretical models of a set of canonical computations such as convolution, 15thresholding, exponentiating and normalization that could be hierarchically repeated to give 16 rise to more complex representations. Another line or research focused on response properties 17 of high-level visual cortex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 92 publications
(112 reference statements)
2
21
0
Order By: Relevance
“…It has been shown that DCNN provides the best model out of a wide range of neuroscientific and computer vision models for the neural representation of visual images in high-level visual cortex of monkeys (Yamins et al, 2014) and humans (Khaligh-Razavi and Kriegeskorte, 2014). Other studies have demonstrated with fMRI a direct correspondence between the hierarchy of the human visual areas and layers of the DCNN (Güçlü and van Gerven, 2015; Eickenberg et al, 2016; Seibert et al, 2016; Cichy et al, 2016b). In sum, the increasing feature complexity of the DCNN corresponds to the increasing feature complexity occurring in visual object recognition in the primate brain (Kriegeskorte, 2015; Yamins and DiCarlo, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…It has been shown that DCNN provides the best model out of a wide range of neuroscientific and computer vision models for the neural representation of visual images in high-level visual cortex of monkeys (Yamins et al, 2014) and humans (Khaligh-Razavi and Kriegeskorte, 2014). Other studies have demonstrated with fMRI a direct correspondence between the hierarchy of the human visual areas and layers of the DCNN (Güçlü and van Gerven, 2015; Eickenberg et al, 2016; Seibert et al, 2016; Cichy et al, 2016b). In sum, the increasing feature complexity of the DCNN corresponds to the increasing feature complexity occurring in visual object recognition in the primate brain (Kriegeskorte, 2015; Yamins and DiCarlo, 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Yamins, DiCarlo and colleagues 39showed recently that using deep networks trained on large-scale object recognition as 40 nonlinear feature spaces for neural system identification works remarkably well in higher 41 areas of the ventral stream, such as V4 and IT [32,33]. Other groups have used similar 42 approaches for early cortical areas using fMRI [34][35][36]. However, this approach has not 43 yet been used to model spiking activity of early stages such as V1.…”
mentioning
confidence: 99%
“…The optimization and cross-validation procedures for Equation 5 were the exact same as those described in Section 2.9, where the learning rate was set to η = 0.001, the stopping criterion was set to ϵ = 0.001 and four-fold cross-validation was performed. This objective function and optimization procedure is similar to that implemented in Seibert et al (2016).…”
Section: Methodsmentioning
confidence: 99%
“…In human neuroimaging studies, recent research has shown that features represented in the shallow layers of a CNN map to fMRI responses in early visual cortex, and features represented in the deeper layers map to responses from higher visual cortex (Güçlü and van Gerven, 2015; Seibert et al, 2016; Wen et al, 2017). Moreover, it has also been shown that stimulus representations in CNNs can be mapped temporally, where peak correspondence between a neural network and MEG responses occurred at earlier time points for shallow layers and at later time points for deeper layers (Cichy et al, 2016; Seeliger et al, 2017).…”
Section: Introductionmentioning
confidence: 99%